1985
DOI: 10.1128/mcb.5.11.2993
|View full text |Cite
|
Sign up to set email alerts
|

The proto-oncogene c-ets is preferentially expressed in lymphoid cells.

Abstract: The transforming sequences of the avian acute leukemia virus, E26, contain two distinct oncogenes, v-mybE and v-ets, fused together. By using a probe containing v-ets sequences, polyadenylated transcripts of the c-ets proto-oncogene were detected in avian tissues; they included a major 7.0-kilobase and a minor 2.0-kilobase species. These c-ets mRNAs were detected at high levels only in lymphoid organs and in avian T and B lymphoid cell lines. A similar pattern of c-ets transcription was observed in human hemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1
1

Year Published

1986
1986
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 26 publications
2
58
1
1
Order By: Relevance
“…Although these data suggest that TCF-2a is identical to c-ets-1, several observations indicate that recognition of the TCF-2e~ site is more complex. First, TCF-2e~-binding activity appears to be restricted to T cells, whereas c-ets-1 is abundant in B cells and macrophages, as well as T cells (Chen 1985;Bhat et al 1989). In addition, Southwestern experiments indicate that TCF-2~ is a 63-kD protein (M.L.…”
Section: Discussionmentioning
confidence: 99%
“…Although these data suggest that TCF-2a is identical to c-ets-1, several observations indicate that recognition of the TCF-2e~ site is more complex. First, TCF-2e~-binding activity appears to be restricted to T cells, whereas c-ets-1 is abundant in B cells and macrophages, as well as T cells (Chen 1985;Bhat et al 1989). In addition, Southwestern experiments indicate that TCF-2~ is a 63-kD protein (M.L.…”
Section: Discussionmentioning
confidence: 99%
“…However, as these cells mature, Erg expression is markedly reduced (Figure 1). The downregulation of Erg during T-cell di erentiation may be necessary for maturation (Barton et al, 1998), as is observed for Ets1 in T cell activation (Bhat et al, 1990;Bories et al, 1995;Chen, 1985;Muthusamy et al, 1995). Expression of Erg during embryonic development of the vascular tree progressively decreases with endothelial maturation.…”
Section: Ets Transcription Factors In Hematopoiesis Vasculogenesis Amentioning
confidence: 99%
“…Preferential expression of Ets1 occurs in B, T and NK cells of adult mice, with high levels in the CD3+ subclass of peripheral T cells (Figure 1) (Barton et al, 1998;Bassuk and Leiden, 1997;Bhat et al, 1989;Chen, 1985). Ets1 is not required for the development of B and T cell lineages, but appears to be essential for their survival and maturation (Bories et al, 1995;Muthusamy et al, 1995).…”
Section: Ets Transcription Factors In Hematopoiesis Vasculogenesis Amentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that a protein with the DNA-binding activity of ets-1 functions as a transcriptional activator. It is reasonable to propose that ets-1 is the EL4 cell protein that functions as an activator of the LTR-mediated expression, since RNA and protein products of the mammalian and chicken ets-1 genes have been reported to be expressed preferentially in lymphoid cells (Chen 1985;Ghysdael et al 1986;Bhat et al 1987Bhat et al , 1989, including mouse EL4 cells. However, if the DNA-binding domain of ets-1 is encoded by the highly conserved region of the ets gene family (as hypothesized above), the data cannot eliminate other ets family members as possible transcriptional activators in EL4 cells.…”
Section: ~Fllelltdks-cqsfis~tg-dgwe-fklsdpde~arr~skrknkpkmnyeklsrglrymentioning
confidence: 99%